2008
DOI: 10.1021/ma702372a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Nanoparticles on the Local Segmental Dynamics in Poly(vinyl acetate)

Abstract: The effect of nanosized silica particles on the properties of poly(vinyl acetate) (PVAc) was investigated for a range of silica concentrations encompassing the percolation threshold. The quantity of polymer adsorbed to the particles ("bound rubber") increased systematically with silica content and was roughly equal to the quantity shielded from shear stresses ("occluded rubber"). This bound and occluded polymer attained a level of ∼12% at a silica volume content of 28%; nevertheless, the glass transition prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
164
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(185 citation statements)
references
References 61 publications
(178 reference statements)
20
164
0
Order By: Relevance
“…67,68 Another difference between the two studies is that while both groups used silica filler, Fragiadakis et al [60][61][62] synthesized the SiO 2 particles in situ by hydrolysis and condensation of tetraethoxysilane, yielding particles having a mean diameter of ~ 10 nm. This is an order of magnitude smaller than the silica used by Bogoslovov et al 64 Whether the appearance of a new dielectric peak in the silicafilled PDMS represents an immobilized phase arising due to the small reinforcing particles or is an artifact of crystallization is an open question. V. CALORIMETRY Differential scanning calorimetry (DSC) yields a direct measure of T g from the abrupt change in the heat capacity upon heating or cooling a sample.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 87%
See 2 more Smart Citations
“…67,68 Another difference between the two studies is that while both groups used silica filler, Fragiadakis et al [60][61][62] synthesized the SiO 2 particles in situ by hydrolysis and condensation of tetraethoxysilane, yielding particles having a mean diameter of ~ 10 nm. This is an order of magnitude smaller than the silica used by Bogoslovov et al 64 Whether the appearance of a new dielectric peak in the silicafilled PDMS represents an immobilized phase arising due to the small reinforcing particles or is an artifact of crystallization is an open question. V. CALORIMETRY Differential scanning calorimetry (DSC) yields a direct measure of T g from the abrupt change in the heat capacity upon heating or cooling a sample.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 87%
“…They reported similar results for an epoxy with added diamond particles. 63 On the other hand, Bogoslovov et al 64 found no change in the shape of the loss peak upon addition of silica particles to polyvinylacetate ( Figure 7). There are differences in these works, which might account for the contrary results.…”
Section: Nuclear Magnetic Resonancementioning
confidence: 94%
See 1 more Smart Citation
“…On the one hand, both experimental and computational results have suggested that a mobility gradient exists near the surface of nanoparticles (NPs) on a small, sub-chain-length scale [370,376,377]. On the other hand, silica NPs have been found to have no influence on the local segmental dynamics of poly(vinyl acetate) chains adjacent to them, when compared with the chains in the bulk [383]. Very recently, Richter and his co-workers carried out extensive neutron spin echo experiments on the dynamics of entangled polymer chains in PNCs [374,375,384].…”
Section: Polymer Dynamics At Interfaces and In Interphasesmentioning
confidence: 99%
“…Likewise, for polymer nanocomposites their glass transition temperatures has been observed to increase, 14 decrease, 15 disappear, 14 or remain unaltered. 16 Although the effects of physical size, confinement, and incorporation of fillers on glass transition temperature have received major attention, physical ageing of these materials has not received adequate investigation. All polymers exhibit significant physical ageing in their glassy state.…”
Section: Introductionmentioning
confidence: 99%